THE SPEAKING SKILLS LEARNING DURING THE COVID -19 PANDEMIC AT THE PBSI STKIP PGRI BANJARMASIN STUDENTS : Indonesian Language and Literature Education Study Program, School Of Teacher Training and Education of The Teachers' Union of The Republic of Indonesia - Ida Komalasari; Erni Susilawati; Novia Winda (Proceeding International Conference on Digital Education and Social Science, 2022)
At the beginning of 2022, the COVID-19 pandemic is still happening. The learning system seems to start to adjust because if it is done online, the results are certainly not optimal. Especially , if it is a practical course such as a speaking skills course. Researchers are interested in researching with the aim of 1) describing cognitive, effective, and psychomotor learning outcomes, 2) describing the implementation of learning, 3) describing the obstacles that occurred and 4) describing the right strategies in learning speaking skills during covid 19 pandemic in PBSI STKIP PGRI (Indonesian Language and Literature Education Study Program, School of Teacher Training and Education of the Teachers' Union of the Republic of Indonesia ) Banjarmasin students. The type of the reasearch is a qualitative of descriptive research. The research subjects are PBSI STKIP PGRI Banjarmasin students who participated in Speaking Skills and the lecturers. Data collection techniques used are through observation, interviews, documentation, and questionnaires. Data analysis techniques were with reduction, presentation, and drawing conclusions. The results showed that 1) Cognitive, effective, and psychomotor learning outcomes have improved very well, 2) The implementation of learning was carried out both offline and online in turn every week to reduce crowds, mandatory mask wearing,.The learning methods used are with lectures, questions and answers, exercises, demonstrations, assignments, and field trips.The media used are Power Point Presentation, YT, cameras, and cellphones.4) The obstacles faced when the learning process of speaking skills, especially during online course were students were often constrained by signals and unpreparedness due to environmental factors 4) good strategies used to learn speaking skills are that students must have a lot of practice and practice, the learning process must have dsmostration and practice, the final test must also be practiced. Henceforth, they must have their own You Tube channel and post activities to practice speaking skills.